Genome Engineering in Livestock: Recent Advances and Regulatory Framework - Kumar, Dharmendra; Kues, Wilfried A. (Animal Reproduction Update, 2022)
Since the domestication of animals, livestock species are an important source of protein-rich food, and other animal products. The very recent progress in genetic engineering allows to modify the genomes of livestock species in an unprecedented way to improve productions traits, disease resistance, adaptation to climate changes, animal welfare aspects, but also to develop large animal models for developmental biology and biomedicine. Here, we concisely summarize the recent progress of genome-editing technologies, with a particular focus on the CRISPR/Cas9 designer nuclease, in livestock. Currently, precision-modified livestock lines with disease resistance and production traits are ready to be introduced into the commercial production. On a scientific basis these lines are considered safe for human consumption, especially for genome edits implementing only a single nucleotide change, which mimic ´natural´ point mutations. Internationally, however, there are clear differences in the interpretation of the legal framework on whether genome edited animals or their products need to be regulated.